Linking cultural intelligence and adaptive performance: do intercultural interactions and Host University Support™ play important roles? - Suharti, Lieli; Handoko, Yohanes Andreanto; Huruta, Andrian Dolfriandra (Business, Management and Economics Engineering, 2019)
Purpose: As the globalization has changed the working environment, organizations need more adaptable individuals who have the abilities to work effectively, deal with unpredictable work situations, and adapt to diverse social contexts. Individuals’ international experience such as being enrolled in a study exchange program has been extensively examined as predictors of adaptive performance. In contrast, the role of cultural intelligence in promoting adaptive performance and the quality of experience itself has been overlooked. This study examined the moderating role of host university support in terms of the relationship between intercultural interactions and cultural intelligence towards adaptive performance.Research Methodology: This study tested its hypothesis with primary data from a sample of 123 university students who have the experience of going abroad as student exchange participants. The primary data was gathered through the structured questionnaires which were sent to the respondents through e-mail, messenger, and social media. The Statistical Package for Social Science (SPSS) 20 for Windows was used to analyze the data.Findings: The regression analysis demonstrated that cultural intelligence, together with intercultural interactions and host university support, was an important predictor of adaptive performance.Research Limitations: All of the data in this study were collected through internet or e-mail which has limited control towards the respondents’ answers. Further, this study did not really consider the respondents’ scope as we welcome everyone who has the experience of joining a study exchange program to participate in this research. Practical Implications: The findings suggested the importance of cultural intelligence as a critical predictor of adaptive performance in multicultural contexts, as well as the host university support and intercultural interaction roles for the development of an individual’s cultural intelligence.Originality/Value: This study complemented the previous assumption on universities’ crucial role in educating and preparing the students to be a part of the global citizens.